Supplier behavior and its impact on customer satisfaction: A new characterization of negotiation behavior. Issue 1 (January 2019) - Saorín-Iborra, M. Carmen; Cubillo, Gustavo
Abstract: Many questions of customer/supplier negotiation dynamics remain unanswered. One reason behind this is that most existing models do not entirely reflect the complex relationship between negotiation behavior and the attained outcome of the negotiation process, analyzing the former from a purely dichotomous perspective. This study examines supplier negotiation behavior and how it impacts the outcome (satisfaction) from the customer´s perspective, thereby proposing a new characterization of negotiation behavior. Our analysis is based on a case study of 21 customer/supplier negotiations carried out by four leading supermarket chains in Costa Rica. Evidence supports our proposal that in customer/supplier negotiations, supplier negotiation behavior can include both integrative and competitive actions within the same negotiation, thereby justifying our proposal of different classifications existing within the negotiation continuum. It was also noted that supplier negotiation behavior influences a customer´s perceived satisfaction level. These findings are relevant to both academia and the professional world and can be used to promote better implementation and performance of agreements attained during a negotiation. Highlights: Proposal of a new characterization of the negotiation behavior. Case study based on 21 customer/supplier negotiations undertaken by the four main supermarket chains in Costa Rica. Integrative and competitive actions are complementary rather than excluding. Supplier negotiation behavior is a key determinant of the customer satisfaction. Suppliers tends to display competitive behaviors rather than integrative.